Development NGOs : understanding participatory methods, accountability and effectiveness of World Vision in Zimbabwe with specific reference to Umzingwane District. - Knight, Kayla Christine (Rhodes University, Faculty of Humanities, Department of Sociology, 2014)
Non-governmental Organizations (NGOs) have occupied a prominent role in the development of rural Zimbabwe since the time of its independence in 1980. NGO work in Zimbabwe currently takes place within the context of a tense and fluid political climate, an economy struggling to recover from crisis, international skepticism toward long-term donor investment in development, and global expectations about the methodologies and accountability measures carried out in intervention-based development work. In the light of the participatory methodologies and empowerment-based development frameworks that dominate the current global expectations for work within the NGO sector, this thesis focuses on the work of one particular NGO working in Zimbabwe, namely, World Vision. The main objective of the thesis is to understand and explain the participatory methods, accountability and effectiveness of World Vision in Zimbabwe (with particular reference to Umzingwane District) and, in doing so, to deepen the theoretical understanding of NGOs as constituting a particular organizational form. World Vision is a large-scale international NGO that has a pronounced presence in Zimbabwe and it is specifically active in Umzingwane District in Matabeleland South Province. The thesis argues that NGOs exist within a complex and tense condition entailing continuous responses to pressures from donors and states that structure their survival. Ultimately, in maneuvering through such pressures, NGOs tend to choose directions which best enable their own sustainability, often at the cost of the deep participatory forms that may heighten the legitimacy of their roles. World Vision Zimbabwe responds to donor trends, national and local expectations of the state and its own organizational expectations by building local government capacity in order to maintain the longevity and measureable outputs of its projects. In doing so, it redefines the concept of participation in pursuing efficient and practical approaches to 'getting things done'. This compromises deep participatory methodologies and, in essence, alters the practices involved in participatory forms in order to maintain World Vision's own organizational sustainability and presence in Zimbabwe.
Keywords: World Vision International; Non-governmental organizations -- Zimbabwe; Non-governmental organizations -- Evaluation; Economic assistance -- Zimbabwe; Economic development -- Zimbabwe; Zimbabwe -- Politics and government -- 1980-; Zimbabwe -- Social conditions -- 1980-; Zimbabwe -- Economic conditions -- 1980-